Perioperative challenges and neuromuscular blockade concerns in robotic thymectomy for myasthenia gravis - Pal,Atish (2020)
Abstract Myasthenia Gravis (MG) is an autoimmune disease characterized by weakness and fatigability of skeletal muscles, with improvement following rest. It is a disease of great significance to the anesthesiologist because it affects the neuromuscular junction. Robotic thymectomy has come up in recent times due to the minimally invasive nature and its advantages. This presents a new set of challenges for the anesthesia team, and here we present the various anesthesia considerations and perioperative management in a series of 20 patients who underwent robotic thymectomy. As it is a recent upcoming procedure, there is a paucity of literature on this topic, and most of the available literature talks about One-Lung Ventilation (OLV) and thoracic epidurals. To our notice, this is the first literature without the use of OLV and thoracic epidural for the management of robotic thymectomy.